Gender-specific diagnostic performance of a new high-sensitivity cardiac troponin I assay for detection of acute myocardial infarction. Issue 1 (1st February 2017) - Schofer, Niklas; Brunner, Fabian J; Schlüter, Michael; Ojeda, Francisco; Zeller, Tanja; Baldus, Stephan; Bickel, Christoph; Lackner, Karl J; Münzel, Thomas; Tzikas, Stergios; Genth-Zotz, Sabine; Warnholtz, Ascan; et al.
Abstract: Background: The determination of cardiac troponin is essential for diagnosing myocardial infarction. A troponin I assay has recently been developed that provides the highest analytical sensitivity to date. Methods: The analysis included 1560 patients with chest pain, of whom 1098 were diagnosed with non-coronary chest pain, 189 with unstable angina pectoris and 273 with non-ST-segment elevation myocardial infarction. The troponin I concentration was determined on admission (0 hours) and 3 hours later. The diagnostic algorithm incorporated troponin I elevation above the gender-specific 99th percentile as well as predefined relative or absolute 3-hour changes in the troponin I concentration (delta). Results: The diagnostic criterion of troponin I above the 99th percentile resulted in a negative predictive value of 98.0% and 98.2% in men and women, respectively. For rule-in of non-ST-segment elevation myocardial infarction, the use of absolute deltas yielded higher positive predictive values and sensitivities compared to relative deltas. With detection rates of about 85% and 82% in men and women, respectively, non-ST-segment elevation myocardial infarction was diagnosed with a positive predictive value close to 84% in men and 80% in women. Conclusions: The investigational troponin I assay provides an excellent non-ST-segment elevation myocardial infarction rule out. With gender-specific differences, the application of absolute changes in troponin concentration was superior to relative changes to rule in patients with non-ST-segment elevation myocardial infarction.